(Nie)rozumienie zjawiska przywództwa w przestrzeni edukacyjnej - Ptak, Małgorzata M.; Śmiałek, Mirosław J. (Studia Edukacyjne, 2021)
In the contemporary and dynamic educational reality, also known as socialization, a young person (or is it just a young one [sic!]) in a process of gaining experience, instead of understanding the environment better with time, gets lost, has problems with self-determination, struggles between the important and the irrelevant, the desired and the redundant, good and harmful. The wisdom and educational experience, the educational process and recognized educational influences should become helpful. The pragmatism of the theory of cognition often allows for conclusions and reflections on every process of scientific cognition. In the area of axiology, it may constitute a “pillar of pedagogical initiation”. In view of the holistic format of the majority of educational phenomena, the subject as a balanced dialogue and consistent in the autonomy of leadership (especially educational!) fits perfectly well the latest theories and trends of modern pedagogical, psychological and social knowledge as well as theories of inter-/intrapersonal management. The above indications are the basis for a wise leadership in education and an upbringing in leadership. Knowledge of leadership issues, understood as the process of socialization, may wisely support and strengthen educational influences. Otherwise, by unwise influences, from the pedagogical point of view, something can be irretrievably lost and wasted. To understand the phenomenon of leadership, you must first thoroughly analyze the issue of leadership in groups, trying to show relationships with other people in the process. This is vital due to the frequent confusion of the concepts of leadership and management, or leadership and command. Leadership is often recognized via its chief attribute by e.g. persistence of community, debates, personalization of tasks and actions, bonds of belonging, dynamisms of interpersonal relations (atmosphere and culture in task situations) and roles as an axiom of task decision-making.